Nutritive Evaluation Of Prawn Waste -Paddy Straw Silage In Cattle - Jose JAmes (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 1993)
Prawn waste was ensiled with chopped paddy straw in equal proportions (1:1 wet basis) using 10 per cent tapioca flour as additive for a period of 50 days. The same proportions of ingredients were mixed and ensiled in smaller silos for 21 days to study the silage characteristics. The prawn waste – paddy straw silage formed after both the periods of ensiling were similar with a characteristic brownish colour and desirable aroma and had no evidence of any fungal growth. Ensiling resulted in an increase in fibre fractions and decrease in crude protein contents, with significant (P < 0.01) differences in nutrient levels between silages after 21 days and 50 days of fermentation. The water soluble carbohydrate content and pH declined significantly (P < 0.01) over different periods of ensiling. The volatile fatty acid proportion in prawn waste – paddy straw silage was optimum after 21 days of fermentation, acetic acid being the predominant one. With increase in period of ensiling, acetic acid levels declined while butyric acid levels increased about five fold, without any change in propionic acid concentration. Trimethylamine levels showed a significant (P < 0.01) increase after different periods of ensiling. Three digestion experiments (Trial 1, 11 and 111) were carried out using six, adult, dry, nonpregnant cows with grass hay (basal ration) alone, grass hay plus paddy straw and grass hay plus prawn waste – paddy straw silage respectively. The overall results of the feeding experiments indicated that prawn waste – paddy straw silage is relished and well digested by cattle as evidenced by a relatively higher feed intake and digestibility coefficients of nutrients. A critical evaluation of the results obtained during the course of the present investigation indicated that prawn waste can be satisfactorily ensiled with paddy straw and tapioca flour as additive and that the material can form a potential alternate feed source for cattle, worth studying in detail.